2014
DOI: 10.1101/cshperspect.a013953
|View full text |Cite
|
Sign up to set email alerts
|

Complex Genetics and the Etiology of Human Congenital Heart Disease

Abstract: Congenital heart disease (CHD) is the most common birth defect. Despite considerable advances in care, CHD remains a major contributor to newborn mortality and is associated with substantial morbidities and premature death. Genetic abnormalities appear to be the primary cause of CHD but identifying precise defects has proven challenging, principally because CHD is a complex genetic trait. Due largely to recent advances in genomic technology such as next-generation DNA sequencing, scientists have begun to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
117
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(119 citation statements)
references
References 37 publications
2
117
0
Order By: Relevance
“…HSD are the most common structural cardiac malformations affecting approximately 1% of live-born and accounts for 50% of congenital heart defects (CHDs). Various epidemiological studies have demonstrated that CHDs have a genetic predisposition as observed in most of the cases [1,2]. Especially, transcription factor genes, primarily NKX2-5, GATA4, and TBX5 have been implicated in regulating the septal development during prenatal stages [3].…”
Section: Introductionmentioning
confidence: 99%
“…HSD are the most common structural cardiac malformations affecting approximately 1% of live-born and accounts for 50% of congenital heart defects (CHDs). Various epidemiological studies have demonstrated that CHDs have a genetic predisposition as observed in most of the cases [1,2]. Especially, transcription factor genes, primarily NKX2-5, GATA4, and TBX5 have been implicated in regulating the septal development during prenatal stages [3].…”
Section: Introductionmentioning
confidence: 99%
“…With clear insight into its aetiology, we may begin to dream of the ways to reduce the incidence of CHD. (8) But here is an exciting new prospect that we, as clinicians, should advocate: to encourage the further elucidation of those factors in the social environments of our patient populations that may be deleterious to heart development, and encourage the introduction of proven factors that reduce the incidence of CHD. In a resource-limited society, social upliftment may be our strongest epigenomic medicine!…”
Section: Resultsmentioning
confidence: 99%
“…(8,10) In the majority, the heart defect is solitary (or sporadic), thus the only congenital defect in a non-syndromic child with no known family history. Until recently these heart defects have posed an enigma: what is the exact cause of the isolated heart lesion when a search for a causative gene often proves to be futile?…”
Section: Casesmentioning
confidence: 99%
See 2 more Smart Citations